Valori e tecniche nel diritto del lavoro - DEL PUNTA, RICCARDO (Studi e saggi, 2022)
The volume collects the papers, duly revised and equipped with footnotes, presented at the conference "Values ​​and Techniques in Labour Law", which was held in Florence on 20 and 21 September 2019, with the ambition to bring together in a single debate, although addressed by different perspectives, the topic of values ​​and that of legal techniques, which often tend to proceed on their own ways, without seizing the reciprocal relationships. The volume is divided into four sections ("The values ​​of labour law", "The employer's powers and their limits", "The dismissals", "The non-standard and flexible contracts"), which explains the diversity of the thematic approaches but also the useful overlaps between the essays and the recurrence of some topics, first of all that of dismissal.